2020
DOI: 10.1093/molbev/msaa223
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpectedly Complex Mitoribosome in Andalucia godoyi, a Protist with the Most Bacteria-like Mitochondrial Genome

Abstract: The mitoribosome, as known from studies in model organisms, deviates considerably from its ancestor, the bacterial ribosome. Deviations include substantial reduction of the mitochondrial ribosomal RNA (mt-rRNA) structure and acquisition of numerous mitochondrion-specific (M) mitoribosomal proteins (mtRPs). A broadly accepted view assumes that M-mtRPs compensate for structural destabilization of mt-rRNA resulting from its evolutionary remodeling. Since most experimental information on mitoribosome makeup comes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 92 publications
(113 reference statements)
0
14
0
Order By: Relevance
“…As a result, very few rRNAs are exposed to the solvent, with proteins coating the entire mitoribosome and stabilizing the fragmented rRNAs (Supplementary Movie 1 ). Proteins follow the classical r-protein nomenclature 21 , and newly identified proteins are numbered according to the last inventory of mitoribosomal r-proteins 22 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As a result, very few rRNAs are exposed to the solvent, with proteins coating the entire mitoribosome and stabilizing the fragmented rRNAs (Supplementary Movie 1 ). Proteins follow the classical r-protein nomenclature 21 , and newly identified proteins are numbered according to the last inventory of mitoribosomal r-proteins 22 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The body protuberance could be assigned to a large insertion in the mitoribosome-specific protein mS45 (Fig. S4B), which shows high structural variability between mitoribosomes in different species despite the conservation of its core domain (Valach et al, 2021). The head protuberance was poorly resolved in our density map but is most likely composed of long extensions of the head's conserved rproteins (uS3m, uS10m, mS35).…”
Section: Discussionmentioning
confidence: 98%
“…As a result, very few rRNAs are exposed to the solvent, with proteins coating the entire mitoribosome and stabilizing the fragmented rRNAs (Movie 1). Proteins follow the classical r-protein nomenclature (Ban et al, 2014), and newly identified proteins are numbered according to the last inventory of mitoribosomal r-proteins (Valach et al, 2021).…”
Section: Overall Structure Of the Chlamydomonas Mitoribosomementioning
confidence: 99%
See 1 more Smart Citation
“…One trait of particular interest is the maximal growth rate of an organism, a fundamental parameter of microbial lifestyle that can tell us a great deal about an organism's ecology [20][21][22]. Among microbial eukaryotes, minimal doubling times range over two orders of magnitude, from hours (e.g., [23,24]) to days (e.g., [25]), and potentially even weeks (e.g., [26,27]).…”
Section: Introductionmentioning
confidence: 99%